2021
DOI: 10.4103/jpbs.jpbs_776_20
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Status and Treatment Needs of Psychiatric Outpatients Aged 18-64 Years in District Civil Hospital, Raichur, Karnataka: A Cross-Sectional Study

Abstract: Background: Psychiatric patients or mentally ill patients conform a substantial section of the community deserving special attention. This study aimed to assess the oral health status and treatment needs of psychiatric patients attending District Civil Hospital, Raichur, Karnataka. Materials and Methods: The study group comprised 150 outpatients aged 18–64 years, attending the Department of Psychiatry, District Civil Hospital, Raichur. A specific questionnaire was drawn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Among the group of patients with special needs, the highest number were those with intellectual disabilities, being studied 8 times [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ], followed by human immunodeficiency virus infection (3 times) [ 21 , 22 , 23 ], and schizophrenia [ 24 , 25 , 26 ] and down syndrome [ 1 , 13 ] (2 times each). Finally, other groups of patients with special needs were only studied once: drug addicts [ 27 ], adult heart transplant [ 28 ], kidney disease [ 29 ], diabetic [ 30 ], autism [ 31 ], psychiatric patients [ 32 ], cerebral palsy, and hemophilia [ 26 ] ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the group of patients with special needs, the highest number were those with intellectual disabilities, being studied 8 times [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ], followed by human immunodeficiency virus infection (3 times) [ 21 , 22 , 23 ], and schizophrenia [ 24 , 25 , 26 ] and down syndrome [ 1 , 13 ] (2 times each). Finally, other groups of patients with special needs were only studied once: drug addicts [ 27 ], adult heart transplant [ 28 ], kidney disease [ 29 ], diabetic [ 30 ], autism [ 31 ], psychiatric patients [ 32 ], cerebral palsy, and hemophilia [ 26 ] ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The highest decayed scores were observed in intellectual disability patients [ 16 , 17 ] (7.55 and 5.52) and HIV patients [ 17 ] (6.86 and 5.36). The highest prevalence of caries was observed in patients with intellectual disability [ 19 , 20 ] (89.4% and 95.5%), followed by psychiatric patients [ 32 ] (87.3%), and schizophrenia [ 25 ] (82.2%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SXI-PL score was higher in patients with normal saliva flow conditions among our population. Patients with mental disorders often have behavioural pattern impairment and an inability to distinguish symptoms of a concurrent physical illness and do not often consider their oral status [5,6]. Thomson et al's (2000) and Hopcraft et al's (2010) presented evidence for oral reactions being drug-induced is variable; both studies demonstrated that hospitalized patients who endured dry mouth symptoms more likely had been exposed to more than two kinds of drugs (cardiovascular, psychiatric and allergy drugs) than those who did not complain of dry mouth.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, some chronic diseases may indirectly affect oral health, as they can lead to reduced motivation regarding oral hygiene and care. For example, psychiatric [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ] and neurological diseases [ 48 , 49 , 50 , 51 , 52 , 53 ], as well as Alzheimer’s disease [ 54 , 55 ], rheumatic [ 56 ], oncological [ 57 ], and cardiovascular diseases [ 58 , 59 , 60 , 61 , 62 , 63 ], can all have an impact.…”
Section: Diseases and Oral Healthmentioning
confidence: 99%